Is high employment in the eurozone possible? Some reflections on the institutional structure of the eurozone and its crisis - Mario Seccareccia (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
The paper analyses some well-known explanations of the eurozone crisis and seeks to provide an answer to the question of whether expansionary fiscal policy is feasible within the restrictive confines of the existing structure of the eurozone. The paper addresses this question by focusing on a very precise historical period, 2008–2009, which immediately followed the global financial crisis and the ensuing Great Recession, to understand what permitted such a sharp rise in government spending throughout the eurozone without triggering a sovereign debt crisis until early 2010.
Keywords: E52; E58; E62; E63; 330; eurozone crisis; fiscal policy; institutional adaptation